Association between the composite dietary antioxidant index and non-alcoholic fatty liver disease: evidence from National Health and Nutrition Examination Survey 2005–2016 - Yidian Fu; Yidian Fu; Chao Jiang; Zonglin Li; Xiangyun Shi; Peiyuan Lv; Peiyuan Lv; Jingbo Zhang (Frontiers in Nutrition)
ImportanceOxidative stress contributes to the progression of non-alcoholic fatty liver disease (NAFLD). Antioxidants from food can reduce NAFLD incidence, and the Composite Dietary Antioxidant Index (CDAI) measures total antioxidant capacity (TAC). However, the relationship between CDAI and NAFLD in the US adult population remains unclear.ObjectiveTo assess whether CDAI is associated with NAFLD in US adults.Design, setting, and participantsThis population-based cross-sectional study used data on US adults from the National Health and Nutrition Examination Survey (NHANES) 2005–2016 cycles. Data were analyzed from January to February 2024.ExposuresCDAI obtained from the dietary intake questionnaire.Main outcomes and measuresThe main outcome was NAFLD which defined by the US fatty liver score (USFLI) ≥30. Sampling weights were calculated according to NHANES guidelines.ResultsAmong 9,746 adults included in this study [mean age, 48.3 years; 4,662 (47.6%) males], 3,324 (33.0%) were classified as having NAFLD using USFLI. In the fully adjusted of multivariable logistic regression, CDAI was negatively associated with NAFLD (odds ratio [OR], 0.95; 95% CI, 0.93–0.98). Furthermore, individuals in the highest quartile of CDAI were 34% less likely to have NAFLD compared to those in the lowest quartile (OR, 0.66; 95% CI, 0.52–0.85). In subgroup analyses, CDAI was inversely associated with NAFLD among participants with a BMI <25 (OR, 0.89; 95% CI, 0.83–0.95) and without metabolic syndrome (OR, 0.93; 95% CI, 0.91–0.96). The interaction tests revealed significant differences in these subgroups (P for interaction = 0.04 for BMI and 0.003 for metabolic syndrome). Sensitivity analyses confirmed this association using the hepatic steatosis index (HSI) to define NAFLD, applying unweighted logistic regression, adjusting for physical activity or after excluding non-Hispanic Black participants, and after excluding medications known for their potential hepatotoxic effects.Conclusions and relevanceIn this cross-sectional study based on six cycles (2005–2016) of the NHANES, CDAI was negatively associated with NAFLD in US adult population. This association highlights the potential for dietary interventions to reduce NAFLD incidence and underscores the need for future research, including clinical trials and mechanistic studies, to further explore the role of dietary antioxidants in NAFLD prevention and management.